EMPATHETIC COSMOPOLITANISM: SOUTH AFRICA AND THE QUEST FOR GLOBAL CITIZENSHIP (The Strategic Review for Southern Africa, 2021)
One feature of Nelson Mandela's legacy in South Africa is his concept of post-apartheid society as a cosmopolitan space. Sadly, recent developments in the country suggest a return to nativist and bigoted world views and cast a dark shadow over his legacy. There is an urgent necessity to review this aspect of Mandela's vision. In so doing, this paper highlights the ethical advantages of cosmopolitanism, and argues that what sets Mandela's cosmopolitanism apart from others is his emphasis on empathy. I therefore suggest that empathetic cosmopolitanism is a particularly South African worldview. In support of this idea of empathetic cosmopolitanism, I discuss such recent theories as 'incompleteness', 'multiple identity', and 'entanglement', suggested by South African thinkers, as registers of Mandela's global citizenship.